Patient and Graft Survival of Kidney Allograft Recipients With Minimal Hepatitis C Virus Infection: A Case-Control Study - Shahbazian, Heshmatollah; Hajiani, Eskandar; Ehsanpour, Ali (Urology Journal, 2008)
Introduction: The impact of pretransplant hepatitis C virus (HCV) infection on the outcome of kidney transplantation is controversial. This study was designed to determine the impact of pretransplant minimal HCV infection on the patient and graft survival at a single center in southwest of Iran. Materials and Methods: We designed a historical cohort study on 337 kidney transplant recipients and selected 35 patients with HCV infection and a histological activity index score less than 4 (minimal HCV infection). A group of kidney recipients with negative anti-HCV antibody were compared with the anti-HCV-positive patients in terms of acute allograft rejection, graft loss, mortality, causes of death, and patient and graft survival. The controls were matched for age, sex, donor source, pretransplant dialysis duration, and panel reactive antibodies test. All of the participants had a follow-up period of at least 5 years. Results: There were no significant differences in terms of early and late acute allograft rejection episodes between the groups. Although patient and graft survival rates were lower in HCV-positive patients at 2 and 5 years, the differences between the two groups were not significant. The main causes of death among patients with and without HCV infection were sepsis and cardiovascular events, respectively.Â Conclusion: Our findings suggest that pretransplant minimal HCV infection had no detrimental effect on the short-term patient and graft survival. However, we suggest that kidney transplant recipients with minimal HCV infection be monitored for severe systemic bacterial infections.